Australian perspecta 1993. - Lynn, Victoria; Perkins, Hetti; Green, Charles; Barnes, Carolyn (Sydney : Art Gallery of New South Wales, 1993)
Abdulla, Ian ; Beevors, Michele ; Bell, Catherine ; Bram, Stephen ; Campbell, Barbara ; Cattapan, Jon ; Deacon, Destiny ; Elliot, Michele ; Groves, Helga ; Johnson, Matthew ; Laing, Rosemary ; Newman, Elizabeth ; Snee, Christopher ; Tyssen, Ingeborg ; Wilson, Gary ; Zika, Paul ; etc.
Australian perspecta 1993, is the seventh in this series of contemporary exhibitions which began at the Art Gallery of New South Wales in 1981.
English
kunstcatalogus
Keywords: Australië